ANALISIS PENGARUH RASIO SOLVABILITAS DAN EFISIENSI PERBANKAN TERHADAP PROFITABILITAS BANK UMUM SYARIAH PERIODE 2016-2020 - Versiandika Yudha Pratama; Alfi Rohmawati (Universitas Islam Negeri Sumatera Utara, 2022)
This study aims to determine the effect of the Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR) and Operating Costs of Operating Income on the Return on Assets (ROA) of Islamic Commercial Banks for the 2016-2020 period. This research is classified as causal research with quantitative approach. The data source used is a secondary data, namely the annual report of Islamic Commercial Banks. With purposive sampling technique, the number of samples obtained is 8 Islamic commercial banks. The data analysis method used in this study is multiple linear regression analysis with hypothesis testing measured through the t test and F test. The results of the study conclude that DER and DAR partially have no effect on the ROA variable at Islamic Commercial Banks in Indonesia in the 2016-2016 period. 2020. Operating Costs of Operating Income variable has an effect on the ROA. Meanwhile, the DER, DAR and Operating Costs of Operating Income variables simultaneously influence the ROA variable for Islamic Commercial Banks in Indonesia for the 2016-2020 period.